Coda: The Open - Michael Palmer (Sillages Critiques)
The notion of the open has a long history in poetry. This article also looks into its present and sketches its future, along a patient, open-ended recollection and reassembly of Robert Duncan and his poetic world. Exploring little known areas in American poetry, namely the 1973 anthology of Open Poetry put out by Ronald Gross and George Quasha, but also Charles Olson’s projective verse project, the full scope of Duncan’s Opening of the Field comes into view as an attempt at a new condition of poetry, as a kind of topological reality, where compositional decisions proceed seemingly from ad hoc pressures as if it too were a form of listening to the text. This journey through the poetic countercultures of the whole second half of the 20th century practices what it preaches. It stands, open, for the reader to range through.